Intangible Capital and Labor Productivity Growth: Panel Evidence for the EU from 1998–2005. (4th February 2013) - Roth, Felix; Thum, Anna‐Elisabeth
<x xml:space="preserve">Abstract</x> Using new international comparable data on intangible capital investment by business within a panel analysis between 1998 and 2005 in an EU country sample, a positive and significant relationship between intangible capital investment and labor productivity growth is detected. This relationship proves to be robust to a range of alterations. The empirical analysis confirms previous findings that the inclusion of business intangible capital investment in the asset boundary of the national accounting framework increases the rate of change of output per hour worked more rapidly. In addition, intangible capital is able to explain a significant portion of the unexplained international variance in labor productivity growth, and becomes a dominant source of growth.